AKIBAT HUKUM TIDAK DILAKSANAKANNYA PENYERAHAN KEBUN KEMITRAAN MANDIRI OLEH PT. POLIPLANT SEJAHTERA KEPADA KOPERASI KUDANGAN MANIS DI DESA HARAPAN BARU KECAMATAN AIR UPAS KABUPATEN KETAPANG - NIM. A1012211147, BETRAN MARSILUS (Fakultas Hukum Universitas Tanjungpura, 2025)
AbstractThe method used in this study is an empirical method by collecting primary data in the form of interviews, with a Descriptive approach, namely by describing and analyzing based on existing facts or data collected as they were at the time this research was conducted. The formulation of the problem in this study is